Connections of the Dorsomedial Visual Area: Pathways for Early Integration of Dorsal and Ventral Streams in Extrastriate Cortex - Rosa, Marcello G. P. (J Neurosci, 2009)
The dorsomedial area (DM), a subdivision of extrastriate cortex characterized by heavy myelination and relative emphasis on peripheral vision, remains the least understood of the main targets of striate cortex (V1) projections in primates. Here we placed retrograde tracer injections encompassing the full extent of this area in marmoset monkeys, and performed quantitative analyses of the numerical strengths and laminar patterns of its afferent connections. We found that feedforward projections from V1 and from the second visual area (V2) account for over half of the inputs to DM, and that the vast majority of the remaining connections come from other topographically organized visual cortices. Extrastriate projections to DM originate in approximately equal proportions from adjacent medial occipitoparietal areas, from the superior temporal motion-sensitive complex centered on the middle temporal area (MT), and from ventral stream-associated areas. Feedback from the posterior parietal cortex and other association areas accounts for <10% of the connections. These results do not support the hypothesis that DM is specifically associated with a medial subcircuit of the dorsal stream, important for visuomotor integration. Instead, they suggest an early-stage visual-processing node capable of contributing across cortical streams, much as V1 and V2 do. Thus, although DM may be important for providing visual inputs for guided body movements (which often depend on information contained in peripheral vision), this area is also likely to participate in other functions that require integration across wide expanses of visual space, such as perception of self-motion and contour completion.